2013
DOI: 10.1016/j.arth.2013.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Is Increased Modularity Associated With Increased Fretting and Corrosion Damage in Metal-On-Metal Total Hip Arthroplasty Devices?

Abstract: This retrieval study documents taper damage at modular interfaces in retrieved MOM THA systems and investigates if increased modularity is associated with increased fretting and corrosion. One hundred thirty-four (134) heads and 60 stems (41 modular necks) of 8 different bearing designs (5 manufacturers) were analyzed. Damage at the shell–liner interface of 18 modular CoCr acetabular liners and the corresponding 11 acetabular shells was also evaluated. The results of this study support the hypothesis that fret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 18 publications
4
115
0
Order By: Relevance
“…Collier et al [8], in a cohort of 411 modular prostheses, reported a positive correlation between corrosion and length of implantation, although the bearing combinations (eg, MoM and MoP) were not reported. Similar results were reported for MoM cohorts [14,20]. Interestingly, Goldberg et al [19] found that although corrosion of the head and neck increased with time, head fretting actually decreased, an effect attributed to etching or buildup of corrosion debris.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Collier et al [8], in a cohort of 411 modular prostheses, reported a positive correlation between corrosion and length of implantation, although the bearing combinations (eg, MoM and MoP) were not reported. Similar results were reported for MoM cohorts [14,20]. Interestingly, Goldberg et al [19] found that although corrosion of the head and neck increased with time, head fretting actually decreased, an effect attributed to etching or buildup of corrosion debris.…”
Section: Discussionsupporting
confidence: 70%
“…Studies with MoM bearings concluded that larger heads are associated with greater fretting and corrosion severity [3,20]. In contrast, recent studies associating head size and corrosion in MoP THAs are conflicting.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In dual modular stems, material coupling and the taper design are also crucial for the micromotion magnitude at the stem-neck junction with titanium neck adapters having significantly higher interface micromotions than those with CoCr adapters [29]. The additional stem-neck junction in dual modular stems has been associated with increased damage at the head-stem junction [22].…”
Section: What Clinical Problems Have Been Reported In Patients With Mmentioning
confidence: 99%
“…Larger head sizes increase torsional forces at the trunnion [9], and this may be a contributing factor in the increased failure rates seen metalon-metal (MoM) THAs [17,22], which have a high revision rate of 19% after 12 years [2]. Increasing head offset and increasing varus neck shaft angle have been considered with head size, leading to an increased effective horizontal lever arm [32].…”
Section: What Clinical Problems Have Been Reported In Patients With Mmentioning
confidence: 99%